Top Team Diversity and Business Performance: Latent Class Analysis for Firms and Cities - Max Nathan (Institute for the Study of Labor (IZA), 2014)
A growing number of studies find linkages between workforce diversity and business performance, but key aspects of this relationship remain unclear. First, within the firm, the role of 'top team' demography on firm outcomes is surprisingly little understood. Second, urban location may amplify firm-level processes, but almost no studies test these firm-area interactions. I deploy English cross-sectional data to explore these issues, using latent class analysis to tackle firm-level heterogeneity. I find evidence of positive links in some firm classes, both linear and non-linear, and suggestive evidence that ethnic top team diversity is amplified in the London city-region.
Keywords: J15; L21; R23; 330; firm-level analysis; business performance; diversity; ethnicity; gender; cities